Penguatan Kompetensi Digital Siswa SMP melalui Workshop Desain Grafis dan Fotografi - Soetam Rizky Wicaksono; Didit Prasetyo Nugroho (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service program aimed to strengthen the digital competencies of junior high school students through a structured workshop on graphic design and photography. The activity was conducted on June 10–11, 2025 at Universitas Ma Chung and involved thirteen students from SMP Insan Amanah accompanied by their teachers. The program was designed based on prior identification of learning needs conducted through coordination with school representatives. The workshop integrated theoretical instruction and hands-on practice covering basic photography concepts such as angle, shot, triangle exposure, and three point lighting, followed by editorial layout training using Canva. Students were guided to edit photographs, arrange layouts, and select appropriate text elements. The results indicated improvements in students’ technical skills, learning engagement, and collaborative behavior. A campus tour conducted at the end of the program provided additional insight into the academic environment of higher education. Overall, the program demonstrated that practice-based learning effectively supports digital skill development among junior high school students.